Ethics, politics and feminist organizing: Writing feminist infrapolitics and affective solidarity into everyday sexism - Vachhani, Sheena J; Pullen, Alison (Human relations (New York), 2019)
This article critically examines a 21st century online, social movement, the Everyday Sexism Project (referred to as the ESP), to analyse resistance against sexism that is systemic, entrenched and institutionalized in society, including organizations. Our motivating questions are: what new forms of feminist organizing are developing to resist sexism and what are the implications of thinking ethico-politically about feminist resistance that has the goals of social justice, equality and fairness? Reading the ESP in this way leads to a conceptualization of how infrapolitical feminist resistance emerges at grassroots level and between individuals in the form of affective solidarity, which become necessary in challenging neoliberal threats to women’s opportunity and equality. Our contribution conceptualizes affective solidarity as central to this feminist resistance against sexism and involves two modes of feminist organizing: the politics of experience and empathy. By addressing the ethical and political demands of solidarity we can build resurgent, politically vibrant feminist organizing and resistance that mobilizes feminist consciousness and builds momentum for change. Our conclusion is that an ethico-politics of feminist resistance moves away from individualizing experiences of sexism towards collective resistance and organizes solidarity, experience and empathy that may combat ignorance and violence towards women.